Multi-modal MRI of mild traumatic brain injury - Narayana, Ponnada A. (Neuroimage Clin, 2014)
Multi-modal magnetic resonance imaging (MRI) that included high resolution structural imaging, diffusion tensor imaging (DTI), magnetization transfer ratio (MTR) imaging, and magnetic resonance spectroscopic imaging (MRSI) were performed in mild traumatic brain injury (mTBI) patients with negative computed tomographic scans and in an orthopedic-injured (OI) group without concomitant injury to the brain. The OI group served as a comparison group for mTBI. MRI scans were performed both in the acute phase of injury (~24 h) and at follow-up (~90 days). DTI data was analyzed using tract based spatial statistics (TBSS). Global and regional atrophies were calculated using tensor-based morphometry (TBM). MTR values were calculated using the standard method. MRSI was analyzed using LC Model. At the initial scan, the mean diffusivity (MD) was significantly higher in the mTBI cohort relative to the comparison group in several white matter (WM) regions that included internal capsule, external capsule, superior corona radiata, anterior corona radiata, posterior corona radiata, inferior fronto-occipital fasciculus, inferior longitudinal fasciculus, forceps major and forceps minor of the corpus callosum, superior longitudinal fasciculus, and corticospinal tract in the right hemisphere. TBSS analysis failed to detect significant differences in any DTI measures between the initial and follow-up scans either in the mTBI or OI group. No significant differences were found in MRSI, MTR or morphometry between the mTBI and OI cohorts either at the initial or follow-up scans with or without family wise error (FWE) correction. Our study suggests that a number of WM tracts are affected in mTBI in the acute phase of injury and that these changes disappear by 90 days. This study also suggests that none of the MRI-modalities used in this study, with the exception of DTI, is sensitive in detecting changes in the acute phase of mTBI.